Perceived Post Partum Stress and Coping Strategies among Postnatal Mothers - Rachel Margret Mathew; Anju Philip T.; Sreejamol M. G. (Technological Innovation in Pharmaceutical Research Vol. 8, 2021)
Background: Postpartum stress is defined as a constraining force produced by postpartum stressors. Postnatal period is the period with increased vulnerability to psychiatric illness, if the mother fails to adopt positive coping strategies. Postpartum period is associated with intense physical and emotional changes leading to anxiety. Objectives: The present study aimed to identify the perceived postpartum stress among postnatal mothers, identify coping strategies adopted by postnatal mothers, find out correlation between the level of perceived postpartum stress and coping strategies among postnatal mothers and find out the association between the level of perceived postpartum stress and demographic variables. Methods: A quantitative descriptive study was conducted among 100 postnatal mothers. Convenience sampling technique was used. Hung postpartum stress scale and coping strategies inventory short form were used for the assessment of postpartum stress and coping strategies. Results: Among the 100 participants, 63% of the postnatal mothers had mild stress, 33% had moderate stress, and only 4% had severe stress. Majority of the mothers were used problem-focused engagement as a coping strategy. There was a positive correlation found between the level of perceived postpartum stress and coping strategies such as emotion-focused engagement and emotion-focused disengagement. There was significant association found between the level of perceived postpartum stress and demographic variables such as age, education, length of marriage, status of pregnancy, method of baby feeding, pregnancy events, intrapartum events, birth weight of baby, child birth experience, status of newborn, and postpartum events. Conclusion: The high proportion and severity of postpartum stress observed among this study group proves that postpartum stress is common and cannot be ignored.